Public and professional writing : ethics, imagination, and rhetoric - Surma, Anne (Palgrave Macmillan, 2005)
This book offers something quite new - an advanced textbook that considers professional writing as a negotiated process between writer and reader. Arguing that ethics, imagination and rhetoric are integral to professional writing praxis, the book encourages students to look critically at various writing practices in a range of contexts.